Likelihood of rural practice in medical school entrants with prior tertiary experience. (3rd July 2019) - Playford, Denese E.; Mercer, Annette; Carr, Sandra E.; Puddey, Ian B.
Abstract: Background: Workforce decisions of medical students with prior tertiary education, relative to those without, are not known. Methods: Rural workforce outcomes for three separate streams of medical students were compared: school leaver entry (SLE) entered medical school direct ( N = 682), non-standard entry (NSE) had some prior tertiary education ( N = 123), and graduate entry (GE) ( N = 317), had a prior completed degree. All students were at least in postgraduate year 3 in 2018, when current urban or rural medical workforce participation was ascertained. Results: Multivariate logistic regression allowing for the influences of rural background, rural clinical school participation, gender, being born overseas, socioeconomic status, and being a bonded rural scholar, showed that NSE students and GE students had increased odds of being in rural practice relative to SLE students. This increase was more than three-fold for NSE students (OR = 3.41, 95% CI 1.94, 5.99, p < 0.001) and greater than two-fold for GE students (OR = 2.54, 95% CI 1.57, 4.10, p < 0.001). Conclusion: Graduates with prior tertiary education were more likely to enter the rural medical workforce than direct school entrants. This suggests that increasing graduate entry programs may augment the rural medical workforce and that undergraduate programs allowing non-standard entry may have the same benefit.